Central Retinal Artery Occlusion Associated with Sildenafil Overdose - Mojtaba Abrishami; Seyedeh Maryam Hosseini; Hamid Mohseni; Majid Razavi; Amir Ghaffarian Mashhadi Nejad; Mohammad Baghi Yazdi; Ghodsieh Zamani (Case Reports in Ophthalmological Medicine)
Background. To report a patient with central retinal artery occlusion (CRAO) associated with sildenafil overdose. Case Presentation. A forty-two-year-old male presented three hours after sudden painless visual loss in the right eye. BCVA was counting finger in two meters, and relative afferent pupillary defect was positive. Fundus examination revealed retinal whiteness except in a limited area of papillomacular bundle and cherry red spot. He consumed two 100 mg film-coated sildenafil tablet (Vizarsin, Krka, d.d., Novo mesto, Slovenia) twelve hours apart, and the last one was six hours before visual loss. He was diagnosed with CRAO with cilioretinal artery sparing. Although we did not find any emboli, anterior chamber paracentesis was done. Four weeks later, BCVA improved to 20/80, with resolving of retinal edema. Cardiovascular, carotid arteries, and neurologic evaluations were negative for any predisposing factor. Conclusion. CRAO is a vision threatening condition that might be associated with the overdose of sildenafil.